The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/pme.12155
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Comorbid Pain and PTSD in Returning Veterans: A Collaborative Approach Utilizing Behavioral Activation

Abstract: These findings suggest that a collaborative approach that includes BA is feasible and a potentially effective treatment for comorbid chronic pain and PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 43 publications
2
67
0
1
Order By: Relevance
“…Our findings suggest that interventions that concurrently address chronic pain acceptance and these co-occurring conditions could be beneficial for reducing disability and improving quality of life. Combined interventions for PTSD and chronic pain have been developed, with preliminary empirical support (Bosco, Gallinati, & Clark, 2013; Otis, Keane, Kerns, Monson, & Scioli, 2009; Plagge, Lu, Lovejoy, Karl, & Dobscha, 2013). These treatments are primarily rooted in cognitive therapies (i.e., cognitive behavioral therapy, cognitive processing therapy), behavioral activation, and interdisciplinary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that interventions that concurrently address chronic pain acceptance and these co-occurring conditions could be beneficial for reducing disability and improving quality of life. Combined interventions for PTSD and chronic pain have been developed, with preliminary empirical support (Bosco, Gallinati, & Clark, 2013; Otis, Keane, Kerns, Monson, & Scioli, 2009; Plagge, Lu, Lovejoy, Karl, & Dobscha, 2013). These treatments are primarily rooted in cognitive therapies (i.e., cognitive behavioral therapy, cognitive processing therapy), behavioral activation, and interdisciplinary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Adult guidelines recommend treating overlapping pain and PTSD symptoms (e.g., fears and avoidance behaviors) concurrently [9,187]. Dually targeted interventions have been developed for adults that combine PTSD behavioral activation, pain education and emphasis on exercise [9,188]. Similarly, other programs developed for adult veterans have combined cognitive processing therapy for PTSD with CBT for chronic pain [9,189].…”
Section: Treatments For Comorbid Chronic Pain In Youthmentioning
confidence: 99%
“…Plagge et al [ 112 ] reported an uncontrolled, retrospective study of 58 US veterans with various chronic pain conditions and PTSD (or signifi cant PTSD symptoms) who were enrolled in an 8-session behavioral activation intervention. Mean duration of chronic pain and PTSD was 7.2 and 5.6 years, respectively.…”
Section: Psychological Treatment Of Comorbid Ptsd and Chronic Painmentioning
confidence: 99%